NCCP Textbook of respiratory medicine - Behera, D; Gaur, SN; Katiyar, SK; Gopal, Bharat; Gupta, KB; Luhadiya, SK (New Delhi, India : Jaypee Brothers Medical Publishers, 2011)
The specialty if the respiratory medicine has advanced rapidly and there is a tremendous growth in its various subspecialities. Scientific knowledge generated in this specialty every year is enormous. As a result, there is rapid advancement in the diagnosis and management of respiratory diseases, in addition to opening of new avenues for research. We are sure the textbook in not the end, but the beginning of a tradition and the subsequent governing body members of the NCCP (1) will continue to update and revise it in future as a continuing educational activity. Shortcomings, if any, will be removed and corrected in subsequent editiond.
1. Physical examination of respiratory system 2. Common clinical symptoms 3. Grow, development and morphology of the respiratory system 4. Normal respiratory physiology 5. Defense mechanisms of the respiratory system and others more
Incluye contents, Index
Keywords: MEDICINE; MEDICINA RESPIRATORIA; PNEUMONIAS; TUBERCULOSIS; LUNG ABSCESS; LUNG CANCER; HIPERSENSITIVE PNEUMONITIS